Кон François Laruelle, Principes de la non-philosophie: Për François Laruelle, Principes de la non-philosophie - Sekulovski, Jordančo; Ahmeti, Lindita (Identities: Journal for Politics, Gender and Culture, 2006)
Author(s): Jordančo Sekulovski | Јорданчо Секуловски Title (Macedonian): Кон François Laruelle, Principes de la non-philosophie Title (Albanian): Për François Laruelle, Principes de la non-philosophie Translated by (Macedonian to Albanian): Lindita Ahmeti Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 5, No 1 (Winter 2006) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 297-299 Page Count: 3 Citation (Macedonian): Јорданчо Секуловски, „Кон François Laruelle, Principes de la non-philosophie“, Идентитети: списание за политика, род и култура, т. 5, бр. 1 (зима 2006): 297-299. Citation (Albanian): Jordančo Sekulovski, „Për François Laruelle, Principes de la non-philosophie“, përkthim nga Maqedonishtja Lindita Ahmeti, Identities: Journal for Politics, Gender and Culture, Vol. 5, No 1 (Winter 2006): 297-299.